Take a Public Speaking Course and Conquer the Fear (Journal of Education and Educational Development, 2021)
The purpose of this research project was to investigate if students today still report a fear of public speaking more often than death and if after completing a public speaking their fears change. Participants in a multi-section public speaking course (N = 374) completed a pre- and post-course survey asking them to select their fears and also complete public speaking anxiety questions. The results showed that pre-course public speaking was chosen more often than death and all other fears except for family tragedy, but after completing the course, the fear of public speaking was no longer selected more than death and was not even among the top five fears students listed. The review of literature also addresses why students should enroll in a basic public speaking course and conquer their fear or anxiety about public speaking while still in college.